The Premature Use of English Grammar by EFL Learners - Nur Mukminatien (TEFLIN Journal: A publication on the teaching and learning of English, 1999)
The roles of conscious learning and error corrections have been questioned since the development of communicative approaches to language teaching, along with theoritical and empirical insights from Second Language Acquisition (SLA) research. Whether overt learning really helps the learner produce better L2 performance is a mistery. This article describes the premature use of English Grammar by EFL learners as shown on their writing performance. It also reviews theoritical insights from SLA theories to uncover the mystery.